Analysis of the Competitiveness in the Agri-food sector: The case of Latin America and the Caribbean Region - Giovanna Maria Borges Aguiar; Jeremias Mate Balogh (Competitio, 2022)
Latin America and the Caribbean (LAC) countries are among the global leaders in the production and exports of agricultural and fisheries commodities, accounting for 15% of the world’s average agri-food export from 1995 to 2019. With rising global market competitiveness, considering the agri-food sector, it is important to assess if the region can compete against other global rivals, and in what products. Accounting for regional potential economic power, remarkable agricultural food export and market expansion, this paper explored the LAC agricultural trade patterns and export competitiveness through the analysis of the Revealed Comparative Advantage (RCA) index, and its modifications - SRCA (Symmetric Revealed Comparative Advantage), RTA (Relative Trade Advantage, and RC (Revealed Competitiveness) - in the agricultural sector for the period of 1995-2019. This paper contributes to the literature by presenting the export characteristics in Latin American developing countries, which can be an important instrument for decision-makers in the agricultural trade policy. Throughout the research period, the results indicated that Brazil, Argentina, and Mexico were the TOP agri-food exporters in LAC. The highest RCA, SRCA, and RTA were found in Guatemala, whereas the greatest RC was found in Argentina. At the product level analysis, oil seeds and oleaginous fruits, miscellaneous grains, seeds and fruit, industrial or medicinal plants, and straw and fodder (HS12) were the most exported items at the 2-digit level. Fruit and nuts, edible; peel of citrus fruit or melons (HS08) had the most competitiveness in the worldwide market, with the highest SRCA and RC indices, whereas coffee, tea, mate, and spices (HS9) had the highest BRCA and RTA values. The evidence suggests that among the TOP 10 exporters in LAC, all indices in the global agri-food trade are said to be relatively stable, whereas survival rates do not persist over time.